Comparisons of walleye pollock, Theragra chalcogramma, harvest [t]o Steller sea lion, Eumetopias jubatus, abundance in the Bering Sea and Gulf of Alaska - Ferrero, Richard C; Fritz, Lowell W; Alaska Fisheries Science Center (U.S.) ([Seattle, WA] : U.S. Dept. of Commerce, National Oceanic and Atmospheric Administration, National Marine Fisheries Service, Alaska Fisheries Science Center, 1994)
Mode of access: Internet.